Structured Writing Assignment: The Teacher’s Strategies And The Students’ Perrception - Nia Dharma Pertiwi; Nur Widiastuti; Betti Widianingsih; Rodiyal Ihsan; Maria Ermilinda Dua Lering; Arief Yanto Rukmana (Journal on Education, 2023)
The structured writing assignment as a learning method in English learning process applied by teacher in the classroom. The research was conducted to know what the teacher’s strategies and the students’ Perception of the Structured Writing Assignment. this research, the researcher used qualitative research, the researcher used observation and interview in collecting data and the thematic analysis in analyzing the data. The respondents in this research were the students of grade ten of A and B and an English teacher. The results of data collection and the data analysis, it showned that the teacher has applied his own design in implementing the Structured Writing Assignment. Those general steps are: (1) Explained the procedure text in details (2) Giving the themes (3) Giving the time limit (4) Evaluating. The students’ perception toward the Structured Writing Assignment were : (1) Assignment which demand the students’ autonomy (2) The presence of the Structured Writing Assignment has made the students interested and felt it is like challenging assignment (3) The Structured Writing Assignment as assignment’s that can improve the students’ vocabularies and grammar capability (4) It can also motivate the students to learn more at home optimally. The students’ problems/difficulties in the structured Writing Assignment are: (1) They lack vocabulary (2) The students have less sources to support their assignment (3) The students claimed that the time limit given by the teacher is not enough. The English teacher was expected to developed creativity and created pleasant condition in teaching/learning process. Then, they were also expected to develop the teaching strategy appropriately for students and design it in implementation the Structured Writing Assignment to be more interesting than before.